Strengthening Peru's Tax Agency - Taliercio, Robert; Engelschalk, Michael (World Bank, Washington, DC, 2012)
The reforms were remarkably successful: by 1997 internal tax revenue had recovered to 13 percent of GDP-despite an extremely difficult political and economic environment-and 90 percent of large corporate taxpayers surveyed believed that taxpayer services had improved. The reforms had several key elements: granting the National Tax Administration Superintendency (SUNAT) meaningful administrative and financial autonomy, implementing radical personnel reform, investing in infrastructure and information technology, and generating public support. The reforms also forged a new relationship between taxpayers and the tax agency and committed to improving services. At the same time, the agency made clear its intention to enforce compliance with the tax code. SUNAT's experience offers several lessons for tax administration reform in other countries. First, the immediate efficacy of SUNAT as a semiautonomous revenue authority was due to a combination of several factors, perhaps the most important of which was a coupling of political leadership with managerial expertise. But Peru's experience also highlights pitfalls to avoid for other countries engaging in tax administration reform.